Internet Marketing as a Tool for the Development of Industrial Enterprises in Modern Economic Conditions - Fomichenko, I.; Barkova, S. (Економічний вісник Донбасу, 2019)
The article highlights the values and the main role of Internet marketing in the activities of an industrial enterprise. The main advantages, composition and segments of Internet marketing are defined. It was determined how the features of the activity in the industrial consumer market influence the development of the Internet marketing strategy. Identified specific aspects of the strategy of Internet marketing, which should be taken into account by enterprises in its development. The key trends in the environment of industrial consumers, formed under the influence of the development and penetration of Internet technologies into the business environment, are investigated. It is proved that the introduction of individual activities of Internet marketing, there is a saving on the marketing costs of the enterprise. The composition and tools of Internet marketing of industrial enterprises of Ukraine are proposed, which should be involved in the Internet marketing strategy of industrial enterprises and ways to use them to improve the efficiency of enterprises: a marketing automation system, a CRM system, a website, search marketing, an online marketplace. content marketing. У статті висвітлено значення та основна роль Інтернет-маркетингу у діяльності промислового підприємства. Визначено основні переваги, складові та сегменти Інтернет-маркетингу. Визначено, яким чином особливості діяльності на ринку промислових споживачів впливають на розробку стратегії Інтернет-маркетингу. Виявлено особливі аспекти стратегії Інтернет-маркетингу, які мають бути враховані підприємствами при її розробці. Досліджено ключові тенденції у середовищі промислових споживачів, сформовані під впливом розвитку та проникнення Інтернет-технологій у бізнес-середовище. Доведено, що при впровадженні індивідуальних заходів Інтернет-маркетингу спостерігається економія на маркетингових витратах підприємства. Запропоновано складові та інструменти Інтернет-маркетингу промислових підприємств України, які мають бути задіяні у стратегії Інтернет-маркетингу промислових підприємств та шляхи їх використання для підвищення ефективності діяльності підприємств: система автоматизації маркетингу, CRM-система, веб-сайт, пошуковий маркетинг, онлайн-маркетплейси, контент-маркетинг. В статье освящены значения и основная роль Интернет-маркетинга в деятельности промышленного предприятия. Определены основные преимущества, состав и сегменты Интернет-маркетинга. Определено, каким образом особенности деятельности на рынке промышленных потребителей влияют на разработку стратегии Интернет-маркетинга. Выявлены особые аспекты стратегии Интернет-маркетинга, которые должны быть учтены предприятиями при ее разработке. Исследованы ключевые тенденции в среде промышленных потребителей, сформированные под влиянием развития и проникновения Интернет-технологий в бизнес-среду. Доказано, что при внедрении индивидуальных мероприятий Интернет-маркетинга наблюдается экономия на маркетинговых затратах предприятия. Предложено состав и инструменты Интернет-маркетинга промышленных предприятий Украины, которые должны быть задействованы в стратегии Интернет-маркетинга промышленных предприятий та пути их использования для повышения эффективности деятельности предприятий: система автоматизации маркетинга, CRM-система, веб-сайт, поисковый маркетинг, онлайн-маркетплейси, контент-маркетинг.